Supraspecific names in spider systematic and their nomenclatural problems [Supraspezifische namen in der spinnensystematik und ihre nomenklatorischen probleme] - Yuri M. Marusik (Arachnologische Gesellschaft e.V., 2022)
Three different types of the names used in spider systematics are recognized and discussed: 1) typified taxonomic names, 2) non-typified taxonomic names, and 3) non-taxonomic names. Typified names are those from genus to superfamily group names; they are regulated by the ICZN. Non-typified names are used for taxonomic groups higher than superfamilies (e.g., Haplogynae, Mesothelae, etc.); they are not regulated by the ICZN but have an authorship, a fixed year of publication and are incorporated in a hierarchical classification. Non-taxonomic names are not regulated by any formal rules, unranked, have no authorship or description, and are non-typified. Some difficulties connected with the non-typified names in spider systematics are briefly discussed. Senior synonyms of some non-typified and non-taxonomic names are discussed, and suggestions are given on how to deal with the non-typified names lacking senior synonyms.